Global REACH: Assessment of Brady-Arrhythmias in Andeans and Lowlanders During Apnea at 4330 m - Busch, Stephen A.; van Diepen, Sean; Steele, Andrew R.; Meah, Victoria L.; Simpson, Lydia L.; Figueroa-Mujíca, Rómulo J.; Vizcardo-Galindo, Gustavo; Villafuerte, Francisco C.; Tymko, Michael M.; Ainslie, Philip N.; Moore, Jonathan P.; Stembridge, Mike; et al. (Frontiers in Physiology, 2020)
BACKGROUND: Ascent to altitude increases the prevalence of arrhythmogenesis in low-altitude dwelling populations (Lowlanders). High altitude populations (ie. Nepalese Sherpa) may have arrhythmias resistant adaptations that prevent arrhythmogenesis at altitude, though this has not been documented in other High altitude groups, including those diagnosed with chronic mountain sickness (CMS). We investigated whether healthy (CMS-) and CMS afflicted (CMS+) Andeans exhibit cardiac arrhythmias under acute apneic stress at altitude. METHODS AND RESULTS: Electrocardiograms (lead II) were collected in CMS- (N=9), CMS+ (N=8), and Lowlanders (N= 13) following several days at 4330m (Cerro de Pasco, Peru). ECG rhythm and HR were assessed at both rest and during maximal volitional apnea (End-Expiratory [EXP]). Both CMS- and CMS+ had similar basal HR (69 ± 8 beats/min vs. 62 ± 11 beats/min), while basal HR was higher in Lowlanders (77 ± 18 beats/min; P<0.05 versus CMS+). Apnea elicited significant bradycardia (nadir -32 ± 15 beats/min; P<0.01) and the development of arrhythmias in 8/13 Lowlanders (junctional rhythm, 3° atrio-venticular block, sinus pause). HR was preserved was prior to volitional breakpoint in both CMS- (nadir -6 ± 1 beat/min) and CMS+ (1 ±12 beats/min), with 2/17 Andeans developing arrhythmias ( 1 CMS+ and 1 CMS-; both Premature Atrial Contraction) prior to breakpoint. CONCLUSIONS: Andeans showed an absence of arrhythmias and preserved HR response to volitional apnea at altitude, demonstrating that potential cardio-resistant adaptations to arrhythmogenesis exist across permanent HA populations. Acclimatized Lowlanders have further demonstrated an increased prevalence of arrhythmias at altitude.